Inducible Bronchus-Associated Lymphoid Tissues (iBALT) Serve as Sites of B Cell Selection and Maturation Following Influenza Infection in Mice - Tan, Hyon-Xhi; Esterbauer, Robyn; Vanderven, Hillary A.; Juno, Jennifer A.; Kent, Stephen J.; Wheatley, Adam K. (Frontiers in Immunology, 2019)
Seasonally recurrent influenza virus infections are a significant cause of global morbidity and mortality. In murine models, primary influenza infection in the respiratory tract elicits potent humoral responses concentrated in the draining mediastinal lymph node and the spleen. In addition to immunity within secondary lymphoid organs (SLO), pulmonary infection is also associated with formation of ectopic inducible bronchus-associated tissues (iBALT) in the lung. These structures display a lymphoid organisation, but their function and protective benefits remain unclear. Here we examined the phenotype, transcriptional profile and antigen specificity of B cell populations forming iBALT in influenza infected mice. We show that the cellular composition of iBALT was comparable to SLO, containing populations of follicular dendritic cells (FDC), T-follicular helper (Tfh) cells and germinal centre (GC)-like B cells with classical dark- and light-zone polarisation. Transcriptional profiles of GC B cells in iBALT and SLO were conserved regardless of anatomical localisation. The architecture of iBALT was pleiomorphic and less structurally defined than SLO. Nevertheless, we show that GC-like structures within iBALT serve as a distinct niche that independently support the maturation and selection of B cells primarily targeted against the influenza virus nucleoprotein. Our findings suggest that iBALT, which are positioned at the frontline of the lung mucosa, drive long-lived and unique GC reactions that contribute to the diversity of the humoral response targeting influenza.